Study of Alternative Mechanisms for Rural Credit Delivery - Blanquita R. Pantoja; Linda M. Pe\~nalba; Maylene L. Adelino; Marie Joy L. Lapis; Flordeliza A. Sanchez (Philippine Institute for Development Studies (PIDS), 1994)
This study aims to identify possible alternative mechanisms of extending credit to agrarian reform beneficiaries (ARB) and to assess the effectiveness, viability and sustainability of the alternative mechanisms for delivering credit assistance to ARBs. It employs two research methods, namely survey and case study and it covers 37 financial institutions and 370 borrowers from regions 6 and 7.
Keywords: 330; agrarian reform; agriculture sector; collateral; credit program; borrower